Insect herbivory dampens Subarctic birch forest C sink response to warming - Silfver, Tarja; Heiskanen, Lauri; Aurela, Mika; Myller, Kristiina; Karhu, Kristiina; Meyer, Nele; Tuovinen, Juha-Pekka; Oksanen, Elina; Rousi, Matti; Mikola, Juha (Nature Communications, 2020)
Climate warming is anticipated to make high latitude ecosystems stronger C sinks through increasing plant production. This effect might, however, be dampened by insect herbivores whose damage to plants at their background, non-outbreak densities may more than double under climate warming. Here, using an open-air warming experiment among Subarctic birch forest field layer vegetation, supplemented with birch plantlets, we show that a 2.3 degrees C air and 1.2 degrees C soil temperature increase can advance the growing season by 1-4 days, enhance soil N availability, leaf chlorophyll concentrations and plant growth up to 400%, 160% and 50% respectively, and lead up to 122% greater ecosystem CO2 uptake potential. However, comparable positive effects are also found when insect herbivory is reduced, and the effect of warming on C sink potential is intensified under reduced herbivory. Our results confirm the expected warming-induced increase in high latitude plant growth and CO2 uptake, but also reveal that herbivorous insects may significantly dampen the strengthening of the CO2 sink under climate warming. Warming is expected to increase C sink capacity in high-latitude ecosystems, but plant-herbivore interactions could moderate or offset this effect. Here, Silfver and colleagues test individual and interactive effects of warming and insect herbivory in a field experiment in Subarctic forest, showing that even low intensity insect herbivory strongly reduces C sink potential. Peer reviewed